SIMPLE VISUAL METHOD FOR IMPROVING CONVERGENCE ANGLE OF PROXIMAL WALLS A COMPARISON STUDY DONE ON MODELS - Dragoș Smărăndescu (Romanian Journal of Oral Rehabilitation)
Ideal convergence angle of axial walls is difficult to achieve clinically especially when multiple abutments are prepared for bridges. Studies have already shown that guided preparation gives better results than non- guided preparation. This paper shows the comparison between non guided and guided preparation on models that were prepared by 17 volunteer dentists.